Anti-poverty programs and presidential election outcomes: Familias en Acción in Colombia (2011)
Using a comprehensive panel data-set for Colombian municipalities, this paper studies the political motives behind the allocation of the largest (cash conditional transfer) anti-poverty program across municipalities in the country, and examines whether the national incumbent governing coalition was rewarded politically for its expansion over the previous decade. Our findings show that, the incumbent governing coalition has used the program to target intensively loyal municipalities. Conversely, evidence supporting the argument that the governing coalition has used the program to target intensively swing regions is not found. We also find that, historically, the incumbent governing coalition has been politically rewarded by the electorate for providing subsidies through the program.